O’ZBEKISTAN NATIONAL UNIVERSITY NAMED AFTER MIRZO ULUGBEK (Ilm fan taraqqiyotida raqamli iqtisodiyot va zamonaviy ta'limning o'rni hamda rivojlanish omillari, 2025)
ABSTRACT: The  aim of this current article  is to expose students to highly engaging opportunities to practice English ,using authentic materials is an excellent option that underpin them and the benefits that still might possibly accrue from experimenting with them. Teachers' perspectives of the use of authentic materials  in learning and teaching. Furthermore, it also  explores some obstacles of using the material.